Eidolon: the shadows and phantasmagoria of a body-spectrum videographic (Móin-Móin Magazine - Studies in the Art of Puppetry, 2021)
This article is an analysis of the creation process of the video Eidolon (2020), an artistic work conducted by the notions of shadow, double and phantasmagoria present in shadow theater, in phantasmagoria shows, in the animation of silhouettes in cinema and in videographic language, to evoke the effects of presence of bodies represented as an image on illuminated, projected and luminous screens. The investigation aims to highlight the poetic potential of the interlocution between ancestral and technological and raise questions about the shadows of the hybrid, the technique, the occult, the desire, and memory in ghost images in contemporary narratives.
Keywords: Shadow; Phantasmagoria; Double; Body; Video